2022
DOI: 10.3390/children9101551
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptions of Sexual Harassment among Adolescents of Four European Countries

Abstract: Sexual harassment is a crucial public health issue among adolescents. In order to develop school health promotion programs, there is a need to involve adolescents themselves paying particular attention to their perceptions, beliefs, attitudes and practices. Therefore, the aim of this study was to explore the adolescents’ perceptions about sexual harassment as well as the ways it could be prevented. Four focus groups were conducted during an online “camp” in autumn 2021, facilitated by members of SHEHAP project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…The same variations in adolescents' perceptions of sexual harassment were reported by other national and international studies (Kabbash et al, Sweeting et al and Sakellari et al (38,39,40) . Many factors could contribute to this wide variation in adolescents' perception of sexual harassment.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The same variations in adolescents' perceptions of sexual harassment were reported by other national and international studies (Kabbash et al, Sweeting et al and Sakellari et al (38,39,40) . Many factors could contribute to this wide variation in adolescents' perception of sexual harassment.…”
Section: Discussionsupporting
confidence: 73%
“…The current study revealed that more than half of the studied adolescent girls reported instilling religious principles and values, proper rearing of children, and imposing legal sanctions on harassers as the most important preventive measures against sexual harassment. Sakellari et al (40) reported other preventive measures included; youth education; adult education for teachers and parents; professional, peer, and family support; official consequences; health education methods regarding the participants' views on the prevention of sexual harassment.…”
Section: Discussionmentioning
confidence: 99%
“…It is fully possible that adolescents’ views on sexual harassment would suggest a further development of the questions that are asked to address this issue. As indicated from a previous study, focus groups might be a good method by which to elicit relevant information based on adolescents’ own views ( 51 ). Furthermore, the associations found between sexual harassment and the psychosocial outcomes may be influenced by other factors not controlled for in the study.…”
Section: Discussionmentioning
confidence: 99%